VALUE OF THE COMPANY : THE MEDIATING RETURN ON EQUITY - Raharja, Indra Pramana (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
The grand theory in this research was built by combining Signal Theory, Stakeholder Theory, and Agency Theory as a conceptual basis for hypothesis development. Signal Theory highlights how information companies convey, such as implementing Good Corporate Governance (GCG), can influence investor confidence and investment decisions. This study aims to analyze the impact of CSR and GCG on company value (Tobin's Q), mediated by financial performance, with a focus on Islamic Social Responsibility (ISR), Independent Board of Commissioners (IBC), and Institutional Ownership (IO). They are using a quantitative method. The data is derived from the annual financial reports of 39 banking companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. The purposive sampling technique was chosen to ensure that the sample used was relevant and could provide valid data to test the relationship between the variables studied and answer the research hypothesis comprehensively. Secondary data was collected from www.idx.co.id, and path analysis was employed as the analytical method. The findings reveal that CSR, ISR, IBC, and IO positively and directly influence company value (Tobin's Q). These results underscore the critical role of CSR and GCG in shaping a company's financial performance and market value.